2024
DOI: 10.1021/acsenergylett.3c02811
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Chemistry of Perfluorinated-Anion Additives Deciphering Ether-Based Electrolytes for Sodium-Ion Batteries

Xin Hou,
Tianyu Li,
Yanling Qiu
et al.

Abstract: Ether-based electrolytes with high reductive stability can be compatible with multiple anodes. However, their low oxidative stability and low flash point lead to restrictions for sodium-ion batteries. Here we report a rational coupling design between perfluorinated-anion additives and cathode/solvent to self-assemble a protective cathode-electrolyte interphase (CEI) and concurrently build a −C−F•••H−C− stable interaction network to promote the stability of ethers. The preferential adsorption and oxidization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The electrolyte, as a crucial component of SIBs, is closely related to the formation of EEI. , Numerous researchers demonstrated that electrolyte design is an effective strategy for constructing a robust NaF-rich EEI, including high-concentration electrolyte, localized high-concentration electrolyte, , all fluorinated electrolyte, , etc. However, the practical application of these electrolyte systems is limited by their expensive cost.…”
mentioning
confidence: 99%
“…The electrolyte, as a crucial component of SIBs, is closely related to the formation of EEI. , Numerous researchers demonstrated that electrolyte design is an effective strategy for constructing a robust NaF-rich EEI, including high-concentration electrolyte, localized high-concentration electrolyte, , all fluorinated electrolyte, , etc. However, the practical application of these electrolyte systems is limited by their expensive cost.…”
mentioning
confidence: 99%